DESIGN OF A WEB-BASED LIBRARY INFORMATION SYSTEM AT STATE VOCATIONAL HIGH SCHOOL 3 OF SOLOK SELATAN - Putra, Dikky Rahmadana; Pernanda, Anggri Yulio (JURTEII: Jurnal Teknologi Informasi, 2024)
The unavailability of the library information system has posed a challenge for librarians in managing a library's inventory, which is susceptible to loss or damage. The objective of this research is to create a system that can assist librarians in managing the library at SMK Negeri 3 Solok Selatan. The research methodology used in designing this system utilizes the System Development Life Cycle (SDLC) with a Waterfall model. It consists of five stages: planning, analysis, design, implementation, and maintenance. Field research processes were conducted through observation and interviews. The test results from the evaluation table of the developed library information system are excellent, with an average evaluation percentage of 91.47%. The criteria include functionality with a percentage of 94.44%, constraints with a rating of 91.67%, system usability with an evaluation of 91.86%, as well as efficiency (95.83%), maintenance (91.67%), and portability (91.47%). This information system may still require updates to its interface and existing information systems since, with the passage of time, new features may emerge to facilitate user access to the information system.